STUDY OF FOOTBALL IN BRAZIL (RIO DE JANEIRO) AND FRENCH (PARIS). (Fiep Bulletin - online, 2013)
The “Comparative study of football in Brazil (Rio de Janeiro) and French (Paris)” tells us the sense that the practitioners of football to give their physical practice in the two countries. Based on the theory of "motor Praxeologism" by Pierre Parlebas, we applied the questionnaire on the views of practitioners in a total of 104 players from football; and 61 in Brazil and 43 in French, with age or older to 15 years. As an outcome of the study, the data show us that the values of sport as culture and sports are present in the responses of participants, both in Brazil and in French. However, the responses of the same show that, while in Brazil, the traditional art of football, learned and practiced alone together, is part of the reality in French, they do with professional football, to compete and win, is a reflection of two different societies.
Keywords: football; values of sport; meaning of practice